Enhanced solar photocatalysis of TiO2nanoparticles and nanostructured thin films grown on paper - Freire, T. (2022)
info:eu-repo/grantAgreement/EC/H2020/787410/EU The work was also partially funded by the Nanomark collaborative project between INCM (Imprensa Nacional - Casa da Moeda). Publisher Copyright: © 2021 The Author(s). Published by IOP Publishing Ltd.